Educational innovations: categories of bulletin board postings designed to increase awareness of contemporary pharmaceutical policy issues - Painter JT; Fink JL III (Centro de Investigaciones y Publicaciones Farmaceuticas, 2010)
Objective: The goal of this project was to categorize and classify bulletin board postings pertaining to pharmaceutical policy from both the professional and lay press. Methods: Bulletin board postings were used to supplement in-class discussion to keep students, faculty and staff up-to-date on emerging trends. A bulletin board located in the main classroom area of the College of Pharmacy Building where students would pass by on the way to class and congregate during break periods was used to display articles from various sources concerning topics related to pharmaceutical policy. Information is presented about the primary subject matters addressed in the articles, the types of publications from which they were drawn, and the top ten sources of articles displayed. Results: This project showed that coverage of issues related to pharmacists is predominantly seen in newspapers and most pertinent issues are business related. Conclusions: It can be seen from this analysis that the issues facing pharmacists are varied. The pharmaceutical policy field is transforming and many of these changes are very relevant to the general population. This is seen from the coverage of all of these issues in the lay press.